Identification of models of complex technical systems under uncertain conditions of the methods of indistinct mathematics in neuronet logical basis - Мінаєв, Ю. М.; Філімонова, О. Ю.; Криксунов, Є. Е. (Proceedings of National Aviation University (archive), 2000)
Considered are problems of determining model parameters of a known structure, the information about model parameters of which is set in the form of indistinct statements, such as <about>, <approximately>, <much more>, etc Proposed is a new algorithm of indistinct mathematics operations realization, on the basis of which has been solved a system of linear algebraic equations for a general case (indistinct coefficients and right-side parts). Such an approach is practically common for majority of linear systems Given are examples illustrating the efficiency if the method